2012
DOI: 10.1002/agr.21293
|View full text |Cite
|
Sign up to set email alerts
|

Crop Production Contracts and Marketing Strategies: What Drives Their Use?

Abstract: Numerous crop marketing and risk management tools are available. Research relating producers' risk attitudes to their use of these tools has produced mixed results, and most studies focus on individual tools, neglecting potential complementarities in information they provide. Little is known about the proportion in which individual tools are used, e.g., the percentage of the crop that is forward sold as opposed to hedged. This study identifies factors, including risk attitude, that impact the proportion of cor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
18
0
2

Year Published

2014
2014
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 37 publications
0
18
0
2
Order By: Relevance
“…Franken et al . () concluded that age, experience, educational level, debt‐to‐asset ratio and risk aversion influenced the use of farmers’ risk management strategies in the United States. Velandia et al .…”
Section: Previous Studiesmentioning
confidence: 99%
“…Franken et al . () concluded that age, experience, educational level, debt‐to‐asset ratio and risk aversion influenced the use of farmers’ risk management strategies in the United States. Velandia et al .…”
Section: Previous Studiesmentioning
confidence: 99%
“…Pourtant, peu d'études s'intéressent aux contrats entre agriculteurs et coopératives dans ce secteur. Si le développement des contrats de commercialisation, comme outil de gestion des risques, a fait l'objet de travaux (Ricome et al, 2008 ;Franken et al, 2012), la diversité des contrats existants demeure mal connue. Cet article contribue à une meilleure compréhension de cette diversité contractuelle en se focalisant plus particulièrement sur les contrats de production.…”
unclassified
“…Papers citing Pennings and Garcia () typically acknowledge the comprehensive approach combining scale and experimental measures of risk attitude and proceed to use one or the other measure individually in their own work (e.g., Franken et al., ; Hudson et al., ; Lusk and Coble, ) or reference the use of factor analysis to combine measures (e.g., Pope et al., ; Tonsor et al., ).…”
mentioning
confidence: 99%